Assertividade : escala multimodal e caracterização do repertório de mulheres inseridas no mercado de trabalho - Teixeira, Catarina Malcher (Universidade Federal de São Carlos, 2015)
The literature on female assertiveness has presented expressive changes in women‟s repertoire throughout the years. It also has started the discussion on the influence of sociodemographic variables in these changes. Thus, it is pertinent to analyze the role of women in a variety of contexts in contemporary society, since a long history of coercion against the female sex has occurred. Allied to this situation, we can affirm that Brazilian studies on social skills, of which assertiveness is a class, are in a period of ascension. However, the studies that specifically discuss assertiveness are still scarce, especially concerning the behavior-analytic approach. In addition, little has been discussed about this matter in Psychology and it is possible to verify a lack of specific evaluation tools on assertiveness produced in Brazil. These findings and considerations are in the foundation of this thesis‟ objectives, which is organized in four studies. The first manuscript aimed to identify and characterize the academic production of national studies on assertiveness, seeking to determine the “state of the art” and describe the development of this research area. The second part sought to analyze the changes in female assertiveness, from the analysis of historical and current contingencies. The third part of the study aimed to construct and validate a scale to assess multimodal assertiveness, encompassing frequency indicators, cultural context and hidden variables as factors associated to this construct. As a result, the unifactorial, 16-item Assertiveness Skills Inventory (IHA, in Portuguese) was produced. It presented high validity in the frequency indicator, measured by internal consistency (α=0,82). The fourth part had the objective of characterizing the assertive repertoire of women and to verify the association of sociodemographic variables with the overall assertiveness score. One hundred and ninety women from the State of Maranhão – higher educated and currently employed in the labor market – have participated in the study. The analysis of all indicators showed higher average scores for the assertive skills „Defend others in group‟ and „Ask friends for help‟ in all indicators, except for „discomfort‟, which showed the highest score for „Approach for sexual intercourse‟. The lowest means of the other indicators concentrated in „Approach for sexual intercourse‟ skill. The data aligns with literature that indicates that the higher the social skills repertoire, the lower the discomfort level and vice-versa. Regarding sociodemographic variables, positive correlation was found for the quantity of undergraduate diplomas and a negative correlation was found for the time of migration from countryside to capital. This means that more higher education degrees and shorter time of migration from countryside to urban area are associated with a higher frequency of assertive ability to self-report. The influence of cultural variables and formal education is discussed to explain assertiveness in this sample. It indicates the need of further research with this population with varied sociodemographic and cultural characteristics. The main contributions of this study are the methodological and empirical references for the analysis of female assertiveness in our country
Assertiveness : multimodal scale and characterization of the repertoire of women inserted in the labor market
Keywords: Relações humanas; Assertividade (Psicologia); Instrumentos de avaliação; Mulheres; Mercado de trabalho; Assertiveness; Woman; Labor market; CIENCIAS HUMANAS::PSICOLOGIA